Metode Pembelajaran dalam Al-Qur’an - Firanita Putri; Ajahari Ajahari (Jurnal Pendidikan Tambusai, 2025)
This study examines learning methods from the perspective of the Qur’an to offer a comprehensive and applicable model in contemporary Islamic education. The study uses a descriptive-analytical qualitative literature study approach by collecting data from Qur’anic verses, hadiths, scholars’ opinions, and modern educational theories. The research population includes relevant literature up to 2025, with a purposive sample of 20-30 main sources. The main instrument is systematic data through reduction, presentation, and inductive conclusion drawing. The study results show that Prophet Muhammad's teaching methods, such as lectures, dialogues, demonstrations, stories, and uswat al-hasanah, emphasize flexibility and patience according to the needs of learners. The principles of tadarruj and problem-based, contextual learning effectiveness are also found to be capable of developing critical thinking skills. Education technology that aligns with Islamic values also supports character formation.In conclusion, this integrated method supports holistic Islamic education that meets the needs of spiritual and cognitive development.